Religion, culture, and autopsy: a survey with muslim religious officials - Avsar, Abdullah; Keten, Alper (The American journal of forensic medicine and pathology, 2019)
The autopsy maintains its significance both forensically and medically despite enormous developments in antemortem and postmortem diagnostic methods. The present study probes the knowledge, attitude, and behavior of religious officials in our city toward autopsy and make an evaluation of how religion and culture affect those factors. - The study consists of 219 Imams (male) and 69 Quran instructors (female) who serve in urban and rural regions of Kahramanmaras and approved informed consent forms. - Two hundred thirty (79%) of the participants stated that the autopsy was an appropriate process according to Islam; 1 (0.3%) stated that it was inappropriate, whereas 57 (19.8%) were observed to have no idea regarding its appropriateness. - The mean knowledge score that participants had about autopsy was determined to be 7.45 ± 1.73 (min = 1, max = 10). - On the other hand, 240 participants (83.3%) stated that it was important for the religious officials to inform the society about the autopsy. - The negative attitude toward autopsy stems from the lack of knowledge and traditions. The religious officials could help the doctors to change the negative attitude stemming from tradition toward the autopsy.
Gesehen am 06.02.2020